Karyotype comparison and characterization of two cauliflower cultivars from Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2023)
Two cauliflower cultivars were karyotyped for correct characterization after orcein staining. Both cultivars have a simple chromocenter type of interphase nuclei and a gradient type of prophase chromosomes, indicating that they descended from a common ancestor. In addition, both strains were found to have 2n=18 chromosomes with an almost identical range of chromosome lengths. In terms of overall length, the white snow cultivar is almost 7 m shorter than the fresh market cultivar, indicating the presence of chromatin length diversification between specimens. In none of the cases was there a noticeable gradual decrease in chromosome length. The metacentric and submetacentric chromosomes were observed in both samples examined. Apart from other karyotypic features, TF, Syi and AsK % indicate the moderately symmetrical nature of the karyotype. As a result, the two cultivars of cauliflower were moderately primitive in nature. The collection of this karyotypic data will aid in the authentic characterization of the two cauliflower cultivars, which is essential information for the breeding program.Jahangirnagar University J. Biol. Sci. 11(1 & 2): 21-30, 2022 (June & December)